Pasalku.ID application: innovative learning media for improving cognitive learning outcomes - Infantri Yunus Brawijaya; Edy Suhartono; Sri Untari (Himpunan Pengembang Kurikulum Indonesia, 2026)
The rapid development of digital learning requires instructional media that can assist students in understanding abstract materials, including the Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. In school practice, many students still struggle to connect constitutional content to real civic contexts, while interactive and structured digital learning media for Pancasila Education remain limited. This study aims to develop Pasalku.ID is a digital learning application designed to enhance students’ cognitive understanding of constitutional materials. The research employed a Research and Development approach using the ADDIE development model. The research subjects included subject-matter experts, media experts, a Pancasila Education teacher, and Grade X senior high school students. Data were collected using expert validation sheets, practicality questionnaires, and pre- and post-test instruments to assess learning effectiveness. The findings indicate that Pasalku.ID is content-valid, practical to use, and effective in improving students’ learning outcomes, as reflected by medium to high N-Gain scores. These results suggest that Pasalku.ID is a feasible digital learning medium for supporting constitutional learning in Pancasila Education. Abstrak Perkembangan pembelajaran digital menuntut tersedianya media pembelajaran yang mampu membantu siswa memahami materi yang bersifat abstrak, termasuk Konstitusi dan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Dalam praktik pembelajaran di sekolah, siswa masih mengalami kesulitan dalam mengaitkan isi konstitusi dengan konteks kehidupan bernegara, sementara ketersediaan media pembelajaran digital yang interaktif dan terstruktur dalam mata pelajaran Pendidikan Pancasila masih terbatas. Penelitian ini bertujuan untuk mengembangkan aplikasi Pasalku.ID sebagai media pembelajaran digital yang dapat meningkatkan pemahaman kognitif siswa terhadap materi konstitusi. Penelitian ini menggunakan metode Research and Development dengan model pengembangan ADDIE. Subjek penelitian melibatkan ahli materi, ahli media, guru Pendidikan Pancasila, serta murid kelas X SMA. Pengumpulan data dilakukan melalui lembar validasi ahli, angket kepraktisan, serta tes pre-test dan post-test untuk mengukur efektivitas pembelajaran. Hasil penelitian menunjukkan bahwa Pasalku.ID valid secara isi, praktis digunakan dalam pembelajaran, dan efektif meningkatkan hasil belajar siswa dengan kategori peningkatan sedang hingga tinggi. Temuan ini menunjukkan bahwa Pasalku.ID layak digunakan sebagai media pembelajaran digital untuk mendukung pembelajaran konstitusi dalam Pendidikan Pancasila. Kata Kunci: hasil belajar kognitif; media pembelajaran digital; Pasalku.ID; pendidikan Pancasila